Demographic Variations of a Modifiable Risk Factor for Hypertension in a Nigerian Rural Community - Jude C., Enebechi; Ngozi R. , Ani (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This reports a survey involving a sample of 300 rural citizens of Obioma in Udi Local Government Area, aimed at determining the demographic variations of a modifiable risk factor for hypertension. Instrument for data collection was a 5-item interviewer administered questionnaire, which was validated by three experts and the reliability was established whose coefficient index value yielded 0.83. The cluster sampling procedure was adopted and conducted in two stages. Stage one involved a purposive selection of ,two villages out of the five villages while the second stage involved drawing of a non-proportionate sample of 150 males and females from each of the two villages using the systematic random sampling technique. Data collected were analysed using frequencies and percentages.· It was found out that differences existed among the various demographic groups in the consumption of alcohol which has been established as a risk factor for hypertension. Finally, the implications for social health promotion were articulated before making recommendations.